1994
DOI: 10.1152/ajprenal.1994.267.4.f632
|View full text |Cite
|
Sign up to set email alerts
|

PKC and high glucose stimulate collagen alpha 1 (IV) transcriptional activity in a reporter mesangial cell line

Abstract: Increased glomerular collagen IV mRNA in streptozotocin-diabetic rats and stimulation of matrix transcripts by high glucose levels in short-term mesangial cell culture provide evidence that stimulation of matrix synthesis is important in early diabetic glomerulopathy. To test whether transcriptional modulation of collagen IV genes is operative, we stably transfected a murine mesangial cell line with a "minigene" expressing luciferase driven by 5'-flanking and first-intron regions of the murine COL4A1 gene to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 0 publications
0
44
0
Order By: Relevance
“…5,9,[41][42][43] Glucoseinduced TGF-␤ expression might directly contribute to increased expression of TGF-␤ in the vascular wall under hyperglycemic conditions. In fact, the in vitro findings of TGF-␤ induction by high glucose concentrations are accompanied by in vivo studies demonstrating increased TGF-␤ expression during hyperglycemia in animal models of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…5,9,[41][42][43] Glucoseinduced TGF-␤ expression might directly contribute to increased expression of TGF-␤ in the vascular wall under hyperglycemic conditions. In fact, the in vitro findings of TGF-␤ induction by high glucose concentrations are accompanied by in vivo studies demonstrating increased TGF-␤ expression during hyperglycemia in animal models of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…3C). These data are particularly interesting given the evidence that high glucose induces de novo diacylglycerol synthesis and subsequent PKC activation in a variety of cell types, including mesangial cells (34,35). In fact, PKC has been identified as a potential therapeutic target in the treatment of diabetic complications (36,37).…”
Section: Enhanced Ctgf Expression In Renal Cortex and Isolated Glomermentioning
confidence: 98%
“…In addition, it has been amply demonstrated that MCs in tissue culture increase the production of fibronectin, laminin, collagen type IV as well as mRNA levels for these matrix proteins when incubated in the presence of supraphysiological concentrations of glucose (7,(15)(16)(17)(18). Although it has been suggested that the increase in matrix synthesis may be partially due to the osmolar effect caused by high glucose concentrations (18), most of the evidence accumulated thus far indicates that the change is related to the metabolism of glucose (16,19,20). Glucose enters MCs by a facilitated diffusion process which is independent of insulin action (21).…”
Section: Introductionmentioning
confidence: 99%